Mindset According to the Qur'an: A Study of Tahlili in Surah Al-Fatihah Verse 7 - Ilmi, Fadilatul; Kuswoyo, Nyoko Adi; Rohtih, Wiwin Ainis; Mahmud, Amir (Literacy: Journal of Education and Social Science, 2024)
Surah al-Fatihah is known by various other names. First, Surah al-fatihah, this surah is the opening surah of the Qur'an and is read in every prayer, as explained by Ath-Thabari. Second, Ummul Kitab, which means